Supply and Demand Analysis of Aeronautical Data Link Communications Based on the Scenario of the MR TBO Demonstration: Focusing on Trajectory-Based Operations in the Digital Era - Nobuo Hongo; Terumitsu Hirata (Aerospace)
This study conducted a basic analysis of the supply and demand of aeronautical data communications, focusing on trajectory-based operation (TBO), which is one of the methods used for improving the efficiency of air traffic in the digital transformation era using a scenario analysis. Based on a multi-regional TBO project conducted in June 2023, this study estimated the communication demand in the TBO era using scenario analysis, analyzed supply capacity using the aeronautical data communication infrastructure that is in use at present and also in the future, and considered the feasibility and challenges of implementation. We found that it is feasible to use a satellite communication system with internet technology for digital flight plans and air traffic control (ATC) instructions such as altitude and speed changes, as exchanged during TBO. We quantitatively clarified that further development of communication technology and ingenuity of transmission methods are necessary for larger-volume data, such as weather images, which is useful for situational awareness. By clarifying the communication performance requirements of the on-board and terrestrial communication systems required in the TBO era, this study contributes to the realization of TBO for stakeholders who make reasonable and timely decisions regarding the investment needed to introduce this technology.